Health education as a tool in the fight against breast cancer: an experience report (Research, Society and Development, 2020)
In Brazil, breast cancer ranks second in terms of neoplasms in the female public. Preventive measures include primary and secondary actions, the primary ones referring to a healthy lifestyle and the secondary ones are more specific, being linked to self-examination, periodic breast assessments and carrying out specific tests, aiming at early diagnosis and increase the chance of a cure. Thus, this study aimed to report a health education action that took place within the scope of primary health care, whose proposal involved the prevention of breast cancer from the prior recognition of its manifestations, as well as the maintenance of healthy habits, aiming at promoting the health of these women. This study is characterized as descriptive with a qualitative approach, an experience report type, based on the use of the Theory of Problematization based on the methodology of the Arch of Charles Maguerez. As main results achieved, it is emphasized that it was possible to sensitize women about the importance of proper self-care, in addition to providing active participation and offering adequate support on the aspects that permeate the disease and its chances of cure through previous diagnosis. Furthermore, it is concluded that the action developed served as a consolidating mechanism of the aspects that constitute health education, reiterating the fundamental function of nursing in the care process.